Optimization of Human Resource Analytics to Support Strategic Decision Making in Modern Talent Management - Abdurrahman Sadikin; Sulistiyanto Sulistiyanto; Berlianingsih Kusumawati; Siti Mahmudah; Ferry Novindra Idroes (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study examines the optimization of human resource analytics in supporting strategic decision making within modern talent management. The research employs a library research approach by reviewing books, scientific journals, research articles, reports, and other relevant literature related to HR analytics, talent management, and strategic decisions. Data were collected through literature review techniques and analyzed using content analysis to identify patterns, relationships, and significant findings. The results indicate that HR analytics plays a strategic role in improving recruitment effectiveness, performance management, employee retention, workforce planning, leadership development, and organizational performance. Furthermore, the study finds that the successful implementation of HR analytics depends on data quality, technological capabilities, analytical competencies, leadership support, and strategic integration. The findings suggest that organizations can enhance decision quality and achieve sustainable competitive advantages by optimizing the use of workforce data. Therefore, HR analytics should be considered a strategic organizational capability that supports evidence-based talent management and long-term business success.